Fracture Resistance and Stress Distribution Pattern of Different Posts-Core Systems in Immature Teeth: An In Vitro Study and 3D Finite Element Analysis - Shahnaz Khadar; Kishor Sapkale; Pravinkumar G. Patil; Sayed Abrar; Manoj Ramugade; Febel Huda (International Journal of Dentistry)
Introduction. Restoration of immature teeth with open apices and thin dentinal walls with conventional post systems remains a challenge. The purpose of this study was to evaluate the fracture resistance of simulated immature teeth restored with different intraradicular posts and assess their stress distribution pattern using 3D Finite Element Analysis (FEA). Methods. Fracture strength testing using universal testing machine was carried out in simulated immature teeth restored with different intraradicular posts grouped as follows: Group A: teeth not restored with posts served as control group; Group B: Cast metal post (CMP); Group C: Customized Composite Post (CCP); Group D: Fiber post (FP). Four 3D FEA models of the above groups were created using CATIATM software and analyzed for stress distribution using ANSYSTM. The results of fracture strength testing and FEA were correlated. Multiple group comparisons were analyzed by one-way ANOVA followed by Tukey HSD post hoc test. Results. The CMP exhibited highest fracture resistance (336.43 N) but resulted in root fractures. The CCP exhibited lower fracture resistance (240.90 N) and favorable stress distribution as compared to CMP. The FP and control group exhibited lower fracture resistance values of 182.69 N and 130.46 N, respectively. The results of 3D FEA demonstrated higher stress concentration in model comprising metallic post and core. Conclusions. Teeth restored with cast metal posts and cores exhibited maximum fracture resistance followed by the customized composite posts, the fiber posts, and the control group. The cast metal posts indicated higher von Mises stresses concentrated in the radicular region; however, the customized composite posts, the fiber posts, and the control group demonstrated stress concentration in the coronal region.